Effect of Seed Colouring with Natural and Artificial Dyes on Storability of Black Gram Seeds - S DAS; S MOHANTY; S K SWAIN (Seed Research, 2026)
An investigation was undertaken in the Seed Physiology Laboratory, Department of Seed Science and Technology, College of Agriculture, Bhubaneswar, to study the effect of seed colouring with few artificial and natural dyes on storability of black gram seeds. Freshly harvested black gram seeds were treated with fungicide (Thiram @ 2g per kg seed), followed by colouring with five artificial dyes @ 0.75% concentration, viz. Aniline blue, Congo red, Methyl violet, Bromocresol purple and Coomasie brilliant blue, and four natural dyes, viz. Beet (root tuber extract), Turmeric (dried rhizome powder), Mehndi (leaf extract), Marigold (extract from petals). One control treatment was also taken, in which only fungicide treatment was given. After colouring, the seeds were dried to moisture content below MSCS (9.0%) and stored in cloth bags under ambient conditions, for a period of 8 months, i.e. from October 2014 to May 2015. Most of the dye treatments, both artificial and natural, had some deleterious effect on maintenance of viability in seeds, as compared to control, though in some cases, the differences were statistically non-significant. None of the dyes had any beneficial effect on germination or vigour parameters. Among the artificial dyes, least deleterious effect was observed in case of seeds treated with Bromocresol purple and Congo red, in terms of various physiological parameters like germinability, percent abnormal seedlings, seed vigour indices and field emergence. Among natural dyes, Mehndi and Marigold treated seeds gave better results than Beet and Turmeric treated seeds, in terms of the physiological parameters. However, seeds coloured with Turmeric showed significantly lower insect infestation throughout the period of storage, as compared to the other treatments and control, clearly indicating its role in control of insect infestation during storage. Maximum deleterious effect of seed physiological parameters was recorded in case of Aniline blue and Methyl violet.